The Effect of Different Positions of Unerupted Lower Third Molar Teeth on the Fragility of Mandibular Angle: Finite Element Analysis - Seyrek, N. K.; Kahraman, O. E. (Wolters Kluwer Medknow Publications, 2022)
Background: The mandibular bone is the largest and strongest bone in comparison to the other bones in the face skeleton. However, it is the most commonly fractured in facial injuries. The location of the fracture in mandible depends on various factors. The relationship of the impacted lower third molar teeth to mandibular angle fracture has been the subject of many epidemiological studies. It is argued that the risk of fracture in mandibular angle is two to four times more when there are particularly an impacted or partially impacted third molar teeth. However, the effect of the position of the impacted tooth on mandibular angle fracture is not clear yet. Aim: This study seeks to reveal the effect of third molar teeth that are impacted in various positions on the angle fragility. Materials And Methods: This study was performed using three-dimensional finite element stress analysis and static linear analysis methodology. Computed tomography (CT) images obtained previously from a patient were used to construct models of the bone tissue. An ILUMA CBCT device (3M Imtec, OK, USA) was used for tomographic scans. Impacted teeth in various positions were digitally modeled separately. Different direction forces were applied to the mandible, the stress values on the bone surrounding the third molar teeth impacted in different positions were determined. Results: Third molar teeth are impacted in mandibular bone in the following positions: mesioangular, vertical, horizontal, and distoangular positions. The study showed that the force that created the highest stress in the Mandibular angle among the modelled groups is the force by ipsilateral angle. Conclusion: For all kinds of impacted teeth, there was more stress accumulation in the buccal area than in the lingual area when the force is from the symphisis.
Keywords: Finite element analysis; impacted third molar teeth; mandibular angle; trauma